Early Adaption of Assessments Using Generative Artificial Intelligence and the Impact on Student Learning: A Case Study - Wang, Ling; Li, Shengchen; Chen, Yue (African Journal of Inter/Multidisciplinary Studies, 2024)
The emergence of generative artificial intelligence (GenAI) has brought new challenges for learners and educators, along with new possibilities. Assessment especially has provided opportunity for innovation using GenAI, but the fast pace of change as technology develops has meant a paucity in the research on the impact of these changes and adaptations. This paper intends to cover this gap by reporting on a case study of a prompt adaptation of GenAI in an assessment in a year-two module in artificial intelligence which is delivered to students in three-degree programmes in a Sino-British university, at the end of 2022. Taking a mixed method qualitative methodology approach, the study collected data from both staff and students, lecturing and studying on the module which was then analysed using NVIVO software. The study highlights that the adapted assessment had a positive impact on the student learning and development experience whilst simultaneously developing within the students an awareness of ethical issues associated with GenAI use. At the same time, it has raised many questions for academic staff, emphasizing the wider impact on learning and teaching that GenAI brings.